2021
DOI: 10.1136/thoraxjnl-2020-215926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quitting smoking on health outcomes during treatment for tuberculosis: secondary analysis of the TB & Tobacco Trial

Abstract: BackgroundDespite treatment, patients with tuberculosis (TB) who smoke have poorer outcomes compared with non-smokers. It is unknown, however, if quitting smoking during the 6 months of TB treatment improves TB outcomes.MethodsThe TB & Tobacco Trial was a double-blind, placebo-controlled randomised trial of cytisine for smoking cessation in 2472 patients with pulmonary TB in Bangladesh and Pakistan. In a secondary analysis, we investigated the hypothesis that smoking cessation improves health outcomes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
14
1
4
Order By: Relevance
“… 47 Smoking cessation also led to better TB treatment outcomes in a secondary analysis of a large tobacco cessation trial in patients with TB in Bangladesh and Pakistan. 48 Our non-significant result for smoking-related outcomes is not consistent with findings from our previous TB study, which used a single MI session and found that the chance of sustained smoking cessation was twice as high in the MI intervention group compared with the control group, 14 although with a less stringent exhaled CO cut-off point. Evidence on the effectiveness of MI for smoking abstinence in non-TB settings has been equivocal.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“… 47 Smoking cessation also led to better TB treatment outcomes in a secondary analysis of a large tobacco cessation trial in patients with TB in Bangladesh and Pakistan. 48 Our non-significant result for smoking-related outcomes is not consistent with findings from our previous TB study, which used a single MI session and found that the chance of sustained smoking cessation was twice as high in the MI intervention group compared with the control group, 14 although with a less stringent exhaled CO cut-off point. Evidence on the effectiveness of MI for smoking abstinence in non-TB settings has been equivocal.…”
Section: Discussioncontrasting
confidence: 92%
“…Conversely, in another study in India, intensive counselling for alcohol disorders led to significantly better TB treatment outcomes in the intervention group compared with the control group 47. Smoking cessation also led to better TB treatment outcomes in a secondary analysis of a large tobacco cessation trial in patients with TB in Bangladesh and Pakistan 48. Our non-significant result for smoking-related outcomes is not consistent with findings from our previous TB study, which used a single MI session and found that the chance of sustained smoking cessation was twice as high in the MI intervention group compared with the control group,14 although with a less stringent exhaled CO cut-off point.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, smoking is associated with delayed smear and culture conversion, along with an increased probability of cavitary lesions [87,89,90]. Recent studies have shown elevated cure rates, reduced transmissibility, and reduced TB recurrence after smoking cessation compared with persistent smokers [91][92][93].…”
Section: Hiv Diabetes and Undernourishmentmentioning
confidence: 99%
“… 31 In recent years, there has been an increasing awareness of the role of tobacco use in inducing TB, 32 the opportunities for TB health professionals to support tobacco cessation, 31 and the improvements observed in TB outcomes as a result of stopping smoking. 33 The emphasis and investment in TB control in SEAR can be further guided to address tobacco use as a key intervention to control TB.…”
Section: Health Consequences Of Tobacco – What Is Missing?mentioning
confidence: 99%